Trend in the Use of Pain Modalities in Patients with Vascular Anomalies - Avalon Yi; Jaimie Linn; Emily Ochmanek; Anna Fabre; MingAn Yang; Aimee C. Smidt (Journal of Vascular Anomalies)
Objective:. To investigate and describe methods of pain management employed by patients at a vascular anomalies clinic (VAC) with the intent to add relevant information on this important topic. Methods:. Patients evaluated from 2011 to 2023 at the VAC at the University of New Mexico were invited to participate. Patients/guardians completed a REDCap survey recording demographics, self-identified diagnosis/type of vascular anomaly (VA), associated pain frequency/severity, pain management tried, and perceived effect(s). Diagnoses were verified/clarified by one of the authors (A.C.S.) when possible. Data was de-identified, analyzed, and reported using descriptive statistics. Results:. In total, 95 patients were included; age range 1–81 years and mean age 22.14 years (sd = 18.43; w/Q1 = 9; Q2 = 16, Q3 = 33). Most common diagnoses were: venous malformation (n = 44) and lymphatic malformation (n = 22). Median pain rating (scale of 0–10) experienced daily was 1; 12% experienced pain daily; 5% 4–5 days a week, 13% 3–4 days a week, and 23% 1–2 days a week. Nonsteroidal anti-inflammatory drugs (32%) and acetaminophen (15%) were the most common over-the-counter medications reported. Nine percent reported using opioids; 9% reported use of cannabinoid-containing products. Of those who used opioids, 33% reported major pain relief pain. Of those who used cannabinoid-containing products, 50% reported major relief in pain. Conclusions:. Pain is common in patients with VA; more than half of participants experienced pain at least weekly, regardless of VA type. Pain management methods varied, including over-the-counter remedies, cannabinoids, and opiates. Specifically addressing pain management in the VAC setting has the potential to positively impact quality of life and safety.